Edukasi Penulisan Artikel Jurnal dan Strategi Publikasi Ilmiah Bagi Mahasiswa Jurusan Ilmu Administrasi Universitas Tanjungpura - Hardi Alunaza; Mentari (I-Com: Indonesian Community Journal, 2024)
In order to avoid problems that often occur and are faced by students regarding the difficulty of scientific writing and publication, it is necessary to provide training that teaches and provides education to students regarding writing scientific articles. This community service was carried out in December using the method of delivering education, questions and answers, and documentation. The aim of implementing this education process is to provide a good understanding for students in administrative science department regarding writing scientific articles and the process of publishing article manuscripts. The results of this activity show that students' lack of knowledge regarding how to write scientifically is the main reason and obstacle for students. Another obstacle faced is that students do not know the applications and tools that can be used to support writing activities. After following the program, students understand better how to write scientific articles and strategies for publishing journal articles.